A CASE STUDY ON SPEAKING ENGLISH AT FOURTH SEMESTER IN PUTERA BATAM IN YEAR 2013-2014 - gaguk rudianto (Universitas Putera Batam, 2014)
Speaking is one of the most important skills in English as a Foreign Language (EFL). Even other people can judge someone whether he masters English or not only by this language skill though there are many other language kills which can decide he master it or not. Of course to judge someone we need to test him or her. There are five kinds of speaking, namely Initiative, intensive, responsive, interactive and extensive. This research used interview speaking test for final examination at the fourth semester in faculty of literature in Putera Batam University. The data collected from the population of 3 classes with the total students of 126 students. The sample is taken from 1 class with the total students of 26. The data from interview are written down in the form of script. Yet not all phases of interview will be analyzed, only probe questions which contain five questions are analyzed from grammar, vocabulary, fluency and Pronunciation.